2017
DOI: 10.1021/acs.macromol.7b01458
|View full text |Cite
|
Sign up to set email alerts
|

Subnanoporous Highly Oxygen Permselective Membranes from Poly(conjugated hyperbranched macromonomer)s Synthesized by One-Pot Simultaneous Two-Mode Homopolymerization of 1,3-Bis(silyl)phenylacetylene Using a Single Rh Catalytic System: Control of Their Structures and Permselectivities

Abstract: Novel well-defined complex polymers, polymers of acetylenetype macromonomers having silylene−vinylene−phenylene−ethynylene hyperbranches, investigated as a new class of subnanoporous oxygen permselective membrane materials, were synthesized very easily by one-pot simultaneous twomode homopolymerization of a single monomer with a single catalyst. For this "simultaneous polymerization" we synthesized AB 2 -type monomers (1,3bis(dimethylsilyl)phenylacetylenes) containing one terminal triple bond and two Si−H grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…In order to confirm the main chain conformations of the three new polymers having one or two carbamate groups (poly( 1 ), poly( 2 ), and poly( 3 )), UV-vis spectra were measured for them, together with poly( 4 ) having no carbamate groups ( Figure 3 ). Since poly( 1 ) and poly( 2 ) showed a similar UV-vis pattern to poly( 4 ), whose main chain had a very tight cis-cisoid conformation maintained by intramolecular hydrogen bonds reported by our group [ 13 , 14 ], we concluded that poly( 1 ) and poly( 2 ) took very tight cis-cisoid conformations. On the other hand, the UV-vis spectrum of poly( 3 ) showed different absorption bands from those of poly( 1 ) and poly( 2 ).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…In order to confirm the main chain conformations of the three new polymers having one or two carbamate groups (poly( 1 ), poly( 2 ), and poly( 3 )), UV-vis spectra were measured for them, together with poly( 4 ) having no carbamate groups ( Figure 3 ). Since poly( 1 ) and poly( 2 ) showed a similar UV-vis pattern to poly( 4 ), whose main chain had a very tight cis-cisoid conformation maintained by intramolecular hydrogen bonds reported by our group [ 13 , 14 ], we concluded that poly( 1 ) and poly( 2 ) took very tight cis-cisoid conformations. On the other hand, the UV-vis spectrum of poly( 3 ) showed different absorption bands from those of poly( 1 ) and poly( 2 ).…”
Section: Resultssupporting
confidence: 76%
“…Most of poly(substituted acetylene)s reported take cis-transoid conformation. On the other hand, the poly(substituted acetylene with two hydroxyl groups)s we reported take cis-cisoid conformation [ 13 , 14 , 15 ]. As a result, they are expected to have a more rigid backbone than cis-transoid poly(substituted acetylene)s. Therefore, cis-cisoid poly(substituted acetylene)s are very promising as better oxygen permeation membrane materials if their processability is good.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations